2014
DOI: 10.1186/1472-6920-14-84
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of internal medicine resident perceptions of graduate medical education following implementation of the 2011 ACGME duty hour standards

Abstract: BackgroundIn 2011, the Accreditation Council of Graduate Medical Education implemented updated guidelines for medical resident duty hours, further limiting continuous work hours for first-year residents. We sought to investigate the impact of these restrictions on graduate medical education among internal medicine residents.MethodsWe conducted eight focus groups with internal medicine residents at the University of Alabama at Birmingham in 06/2012-07/2012. Discussion questions included, “How do you feel the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(13 reference statements)
0
4
1
Order By: Relevance
“…On the other hand, Nevin et al found that the implementation of the AGMCE duty hours rule was associated with fewer hours spent in the hospital, which inevitably decreased hands-on clinical education. 34 In our study, there was no change in the average weekly working hours per resident and fewer working hours violations in the 12-hour on-call system. Reduction in the working hour violations without affecting the average working hours per week led to improved QoL, education, research, and surgical experience among the urology residents.…”
Section: Discussioncontrasting
confidence: 47%
“…On the other hand, Nevin et al found that the implementation of the AGMCE duty hours rule was associated with fewer hours spent in the hospital, which inevitably decreased hands-on clinical education. 34 In our study, there was no change in the average weekly working hours per resident and fewer working hours violations in the 12-hour on-call system. Reduction in the working hour violations without affecting the average working hours per week led to improved QoL, education, research, and surgical experience among the urology residents.…”
Section: Discussioncontrasting
confidence: 47%
“…24,25 Participant comments around potential shiftwork mentality in US trainees are consistent with the literature on the effect of work hour limits and differences in perceptions by US trainees and faculty. [26][27][28][29][30] Themes and Culture of Medical Training and Practice…”
Section: Themes and Acgme Core Requirementsmentioning
confidence: 99%
“…This contrasts with the views of US trainees, who value the improved work-life balance afforded by work hour limits, 33,34 though the comments of US faculty on work hour limits are more ambivalent. 27,30 The Japanese self-sacrifice that extends through one's medical career has been explained as a core quality of Bushido, the moral code that characterized samurai behavior; while Japanese society is changing, this heritage continues to influence physicians and patients' expectations of them. 35,36 Intertwined with this attitude is the Japanese tradition of afterhours socializing with bosses and coworkers.…”
Section: Themes and Acgme Core Requirementsmentioning
confidence: 99%
“…A literature review revealed numerous studies evaluating the training of registrars in other specialties in countries around the world. 6,7,8 There are also examples of studies that have been conducted in developing countries, such as India, specifically assessing the training of ophthalmologists. 9 There are no published studies on this topic of ophthalmology training in South Africa.…”
Section: Settingmentioning
confidence: 99%